Successful treatment with docetaxel plus nintedanib in a patient with lung adenocarcinoma and pulmonary fibrosis: A case report and literature review - Zlatanova, Tanya; Arabadjiev, Jeliazko; Kirova-Nedyalkova, Galina; Nikova, Diana (Frontiers in Oncology, 2022)
Despite the rare incidence of idiopathic pulmonary fibrosis (IPF), coexisting IPF and lung cancer is common. Both diseases have unfavorable outcomes and are often associated with impaired quality of life. In this study, we present a clinical case of a patient with coexisting IPF and lung adenocarcinoma who was successfully treated with nintedanib plus docetaxel as a second-line treatment, and achieved a substantial improvement in the quality of life. To our knowledge, very few cases in the literature address the concurrent treatment of both diseases, which makes this case a valuable illustration of a successful treatment strategy and a basis for future investigations.